Taxonomy,Distribution and economic importance of Xylocarpus species at Carey Island - The heritage island of Malaysia. - Haron, N.W.; Mat Taha, R. (2009)
The genus Xylocarpus, belonging to the family Meliaceae is distributed in the tropics including mangrove habitat from Africa to Australia, Malaysia and India (Ridley, 1922). It is usually associated with Avicennia, Excoecaria, Acanthus, Rhizophora, Bruguiera,Sonneratia, Nypa and Ceriops. There are three species of Xylocarpus in Malaysia namely, Xylocarpus granatum, X. mollucensis and X. rumphii. They are considered important endangered mangrove species in Malaysia. X. granatum, commonly known as nyireh bunga, is important economically for wood carving. The inner bark is a source of dye for tanning, the oil from seeds is used for grooming hair, the fruits and seeds are used to treat diarrhea, and a bark decoction for cholera. It has been mentioned as the best and most beautiful cabinet wood. Its fine, glossy texture is suitable for furniture (Burkill, 1966; Primavera et. al, 2004). However, the population of the species is dwindling hence there is an urgent need to conserve the species. To date, there is no record on detailed morphological study of the species therefore it is one of the aims of the study to investigate the morphological characteristics of the species. Anatomical studies on the leaf were also carried out. Scanning electron microscope study revealed the presence of sunken, anomocytic-type stomata on the abaxial and adaxial surface of the leaf. Results from anatomical studies showed the presence of thick cuticle on both abaxial and adaxial surface of the leaf. Sunken stomata and thick cuticle are adaptations of mangrove species to reduce transpiration. Tannin cells were also observed in the leaf lamina. Regeneration of this species from tissue culture had been attempted, however, only callus formation was observed.